2015
DOI: 10.1021/acs.est.5b03637
|View full text |Cite
|
Sign up to set email alerts
|

Monohydroxylated Polybrominated Diphenyl Ethers (OH-PBDEs) and Dihydroxylated Polybrominated Biphenyls (Di-OH-PBBs): Novel Photoproducts of 2,6-Dibromophenol

Abstract: Hydroxylated polybromodiphenyl ethers (OH-PBDEs) are emerging aquatic pollutants, but their origins in the environment are not fully understood. There is evidence that OH-PBDEs are formed from bromophenols, but the underlying transformation processes remain unknown. Here we investigate if the photoformation of OH-PBDEs from 2,6-dibromophenol in aqueous solution involves 2,6-bromophenoxyl radicals. After UV irradiation of an aqueous 2,6-dibromophenol solution, HPLC-LTQ-Orbitrap MS and GC/MS analysis revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…On the oxidative treatment of BrPs, the formation of brominated polymeric products, such as hydroxylated polybrominated diphenyl ethers (OH-PBDEs) and hydroxylated polybrominated biphenyls (OH-PBBs), becomes an important issue. Several studies have reported that OH-PBDEs and/or OH-PBBs can be appreciably generated from precursor BrPs when treated by Mn­(VII), naturally occurring manganese oxides, photolysis, , or enzymes-mediated oxidation. , These brominated polymeric products have altered or enhanced toxicological effects (e.g., disruption to thyroid hormone homeostasis, disruption to sex hormone steroidogenesis, and neurotoxicity) in comparison to parent compounds, and hence, their occurrence in natural environments and engineered processes has raised great concerns.…”
Section: Introductionmentioning
confidence: 99%
“…On the oxidative treatment of BrPs, the formation of brominated polymeric products, such as hydroxylated polybrominated diphenyl ethers (OH-PBDEs) and hydroxylated polybrominated biphenyls (OH-PBBs), becomes an important issue. Several studies have reported that OH-PBDEs and/or OH-PBBs can be appreciably generated from precursor BrPs when treated by Mn­(VII), naturally occurring manganese oxides, photolysis, , or enzymes-mediated oxidation. , These brominated polymeric products have altered or enhanced toxicological effects (e.g., disruption to thyroid hormone homeostasis, disruption to sex hormone steroidogenesis, and neurotoxicity) in comparison to parent compounds, and hence, their occurrence in natural environments and engineered processes has raised great concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that marine bacteria can synthesis PBDEs using flavin-dependent brominases [ 19 ]. Another source of PBDEs could be photodegradation of bromophenols [ 20 ]. Oral, dermal, and inhalation exposure are all possible routes of PBDE exposure [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…BA was employed to carry out the competition kinetics experiments due to its negligible photolysis under UV irradiation, and TBA was employed to quench HOc in the UV/PDS process to obtain single SO 4 c À oxidation. The second-order reaction rate constants of BPs with SO 4 c À and HOc were calculated via eqn (2) and 3; here, the second-order reaction rate constants of BA with SO 4 c À (k SO 4 c À ,BA ) and HOc (k OHc,BA ) were reported to be 1.20 Â 10 9 M À1 s À1 and 5.90 Â 10 9 M À1 s À1 , respectively. 27…”
Section: Degradation Kinetics Of Bps and Cps In The Uv/pds And Uv/h 2mentioning
confidence: 99%
“…Halogenated phenols (HPs) are typical halogenated compounds that have received increasing attention in recent years due to their potential hazards to water environments and human health. 1,2 Halogenated compounds have been widely used as brominated ame retardants, refrigerants, preservatives, etc. 3,4 With the high production and usage of halogenated compounds, large amounts of HPs (e.g., bromophenols (BPs) and chlorophenols (CPs)) are released from those compounds and discharged into water environments.…”
Section: Introductionmentioning
confidence: 99%